Հայ գրատպությունը և Շուշին - Բաբայան, Օֆելյա (ԱրՊՀ հրատ․)
Армянский печатник Акоп Мегапарт в1512г. в Венеции напечатал первую армянскую книгу <<Урбатагирк>>.Во многих странах мира создавались армянские типографии, армянские книги печатались и во многих не армянских типографиях. Армянское книгопечатание особенно развивалось в 19-ом веке.Среди армян Кавказа первые типографии были созданы в Тифлисе (1823), в Шуши (1827), в Шемахи (1856), в Баку (1872). В Эчмиадзине первая книга была напечатана в 1838г. В 1870-ые года открылись типографии в Гандзаке, Ереване, Александраполе. В Шуши первыми издателями были базельские мисс-сионеры. В годы их деятельности в Шуши были напечатаны 13 книг. Типографию мисссионеров купил и продолжил книгопечатание глава епархии Карабаха Багдасар Митрополит. В 1880-ые годы в Шуши ОТК-рылась и скоропечатанная типография Мирзаджана Акопяна, а также типография Тер-Саакяна. В начале 20-ого века была основана типография Бабаджаняна. Армянское издательское дело в Шуши продолжалось до 1920г., до разрушения армянской части города. Сегодня Шуши востанавливает свой национальный облик, вновь становится центром армянской культуры. In 1512 the first Armenian printer, Hakob Meghapart in Venice, printed the first armenian book «Urbatagirk». In many countries of the world crea-ted by the armenian typography, armenian books printed in many not Armenian typographies too. Armenian printing increased especially in the 19th century. Among the Armenians of the Caucasus first printing press were established in Tiflis (1823), Shushi (1877), then in Shamakhi (1856), in Baku (1872). The first book was published in Etchmiadzin in 1838. In the 1870, s had opened typographies in Yerevan, Gandzak and Alexandropol. In Shushi the first publishers were Basel missionaries. In the course of their work in Shushi were printed 13 books sufficiently processed by ashharabar. A printing press of missionaries bought and con-tinued the typography the head of the Diocese of Karabakh Metropolitan Baghdasar. In the 1880, s in Shushi was opened fast printing press of Hakobyan Mir-zhadzhana, pilgrims in Yеrusalem and Ter-Sahakyan, s printing press. In the early 20th century based the typography of Babajanyan Armenian pub-lishing in Shushi continue until 1920, until destruction of the Armenian part of the city. Today Shushi restore its national image gradually becomes cen-ter of Armenian cultury.
Keywords: Գրատպություն; Արցախ